Quality of reporting of outcomes in trials of therapeutic interventions for pressure injuries in adults: a systematic methodological survey - Miranda, Jéssica Steffany (Int Wound J, 2020)
Randomised controlled trials of therapeutic interventions for pressure injuries should include a clear description of outcomes to increase transparency and replicability and improve the construction of scientific evidence. The objective of this study was to assess the completeness of the descriptions of the outcomes of therapeutic interventions in adults with pressure injury (PI) and factors associated with completeness. This was a systematic methodological survey. The completeness of the outcome was assessed according to five criteria: domain (title), specific measure (technique/instrument used), specific metric, or format of the outcome data of each participant that was used for analysis, aggregation (method data from each group were summarised), and time that was used for analysis. Sixty‐eight studies were included for analysis. A total of 265 outcomes were reported, and 46 trials (67.6%) had 73 primary outcomes, which were mainly intermediates/substitutes (78.8%). The main outcome evaluated was the ulcer area reduction (36.6%). Approximately 37.2% of the outcomes were incompletely reported, and the least described element was the data aggregation method (72.8%). Only 48.4% of the outcomes with the specified technique had the same reference or validation. Poor quality of reporting outcomes was associated with studies with an older year of publication and a small sample size, single‐center studies, and those sponsored by industry. PI studies use many outcomes, mostly surrogates or intermediates, and some of them are incompletely described.